During The COVID-19 Pandemic, The Radiology Department's Infection Control And Radiation Safety Procedures (Journal of Namibian Studies : History Politics Culture, 2022)
To protect patients and stop the COVID-19 virus from spreading further, radiology staff members need to be well-versed in radiation protection and infection control procedures. This study examined how well radiation protection and infection control protocols were followed during COVID-19 mobile radiography.Techniques: From September to December 2021, an online survey was used for a cross-sectional study. During mobile radiography for COVID-19 patients in the study, information on demographics, radiation protection compliance, and infection control practices were gathered. a representative sample of radiologists employed by COVID-19 centers in the United Arab Emirates. In conclusion, it is advised to provide ongoing direction, instruction, and monitoring in order to improve adherence to infection control and radiation protection regulations. To close the practice and knowledge gap, professional associations and educational institutions must work together to offer radiology practitioners structured training programs.